Characterization of secondary deposits of columbite-tantalite minerals found in the city of Rorainópolis (RR), Brazil - Pinto, Anna Caroline Andrade; Maia, Tiago Felipe Arruda (International Journal for Innovation Education and Research, 2020)
Many of the studies about mineral deposits are bringing great information to the scientific community, providing, for example, general characteristics of these deposits, possible source areas and its used in some cases as prospective tools to help in geological mapping. In this way, this study aimed to characterize the alluvial secondary deposits of columbite-tantalite that were found near vicinal 12, about 50km north/northeast of Rorainópolis city, between the BR-174 and BR-210 roads, in the state of Roraima (Brazil), bases on 4 samples that were brought by a resident of the region. To fulfill these objectives, some chemical and mineralogical methods were performed, like: magnetic separation, X-ray diffraction, X-ray fluorescence and petrographic description. The deposits of the region end up being characterized by having a large amount of Fe and Ti (mostly), containing in some places also a large concentration of Niobium and Tantalum. Not all samples have columbite-tantalite, showing that their concentration in some areas of the deposit is quite low. There are samples with less than 1% Nb and Ta and also samples with more than 20% Nb and 6% Ta concentration. These minerals were poorly transported, being identified by the degree of roundness and granulometry of the samples. A weathering cap on some minerals could also be verified. This research work turned out to be relevant, as it provides new data that add to the knowledge of the mineral potential, which has not been fully explored yet.